Level of Students' Knowledge Regarding Scabies Incidents - Khasanah, Almar'ah Uswatun; Imamah, Ida Nur (Poltekkes Kemenkes Aceh, 2024)
Background: Scabies is a type of contagious skin disease caused by the Sarcoptes scabiei mite. There are around 130 million people worldwide affected by scabies to date and scabies usually occurs in relatively densely populated places, such as prisons, orphanages, and Islamic boarding schools. Transmission occurs through direct contact with the sufferer's skin and if this disease is left untreated, secondary bacterial infections can occur due to scratching wounds in sufferers. Purpose: To find out the level of knowledge of students regarding scabies incidents at the Imam Syuhodo Modern Islamic Boarding School. Methods: The type of research used in the study is descriptive research with quantitative analysis, where the sampling technique is carried out using the Quota Sampling method with a total of 89 respondents who are students of the Modern Imam Syuhodo Islamic Boarding School. The research instrument used is a questionnaire on knowledge about scabies. Results: The research shows that there are 39 students (43.8%) who have good knowledge, then 45 students (50.6%) who have sufficient knowledge, and 5 students (5.6%) who have less knowledge. Conclusion: The level of knowledge of students regarding scabies cases at the Imam Syuhodo Modern Islamic Boarding School shows that most of them have sufficient knowledge.